Method for producing cast aluminum-silicon alloy through precise gradient cooling centrifugation of aluminum-silicon raw materials
Through the precise gradient cooling centrifugal process, the problems of difficult furnace conditions, low raw material utilization, high production costs and serious environmental pollution in the existing aluminum-silicon smelting technology are solved, and efficient separation and high-quality production of aluminum-silicon alloys are achieved.
Patent Information
- Application Number
- CN202310976714.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum-silicon smelting technology has problems such as difficult furnace conditions, low raw material utilization rate, high production costs, and serious environmental pollution, and it is difficult to effectively utilize rich silicon-aluminum raw materials.
By using the precise gradient cooling centrifugal process, after crushing silicon aluminum raw materials and carbon reducing agent, binder and water are added for uniform mixing, and then reducing reaction is carried out in an arc furnace, followed by gradient cooling and centrifugal separation to achieve Solid-liquid separation to obtain cast aluminum-silicon alloys that meet industry standards.
Through precise control of the cooling mechanism and centrifugal separation process, effective separation of the silicon phase and the iron phase is achieved, the quality and added value of aluminum-silicon alloy are improved, production costs are reduced, and environmental pollution is reduced.
Smart Images

Figure CN119433194A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of smelting technology, and in particular relates to a method for producing cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials. Background Art
[0002] Aluminum is an important basic material for traditional industries. With the vigorous development of modern industry, modern science and new technologies, silicon and silicon-containing materials have become increasingly important basic materials, and their applications have been popularized in various modern industrial fields such as automobiles, ships and aviation. Bauxite is an important source of aluminum in modern industry. However, my country's bauxite resources are small, and the supply of bauxite has been unable to meet domestic demand for a long time. According to statistics, in the distribution of global bauxite resource reserves in 2021, China's bauxite reserves accounted for only 3.13% of the world. my country's bauxite production has begun to show a downward trend since 2017. According to statistics, my country's bauxite production in 2021 was 85 million tons, a year-on-year decrease of 8.3%. In addition, although my country is rich in silicon ore resources, with the rapid development of the industrial silicon industry and the need for environmental protection, the available resources have also been sharply reduced. Industrial silicon is mainly produced by electrothermal reduction, that is, silica and carbon reducing agent are crushed to a certain particle size, mixed and put into mineral heat for smelting, wherein the reducing agent used is mainly wood blocks, and a certain amount of petroleum coke and washed coal are added. The furnace conditions in the production process of this method are prone to fluctuations and difficult to control, and the raw material utilization rate is low, the production cost is high, the power consumption is high, the product quality is difficult to improve, the smoke and dust emissions are large, and the impact on the surrounding environment is large. In addition, wood blocks need to be added during the smelting process, which will consume a large amount of forest resources and cause damage to the ecological environment.
[0003] Therefore, it is of great economic significance to find alternative aluminum silicon raw material resources. In fact, my country has many types of aluminum silicon raw materials with rich reserves. In addition to bauxite, clay, kyanite, fly ash, coal gangue, etc. are all aluminum silicon raw materials with high aluminum silicon content, especially fly ash and coal gangue. Because the aluminum and silicon in them are difficult to separate, they are usually difficult to be used to produce aluminum silicon products. Chinese patent CN202011267925.4 provides a method for preparing aluminum silicon iron alloy using high aluminum fly ash and graded purification. Chinese patent CN202011267903.8 provides a method for preparing aluminum silicon iron alloy using high aluminum coal gangue and graded purification. Both patent documents mention the method of preparing aluminum silicon iron alloy blocks and graded purification to obtain cast aluminum silicon alloy.
[0004] The present invention attempts to improve the method for preparing cast aluminum silicon alloy on this basis. Summary of the invention
[0005] The technical solution adopted by the present invention to solve the technical problem is:
[0006] A method for producing a cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials, comprising the following steps:
[0007] (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt;
[0008] (2) Under controlled cooling conditions, the obtained aluminum silicon iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 0-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min;
[0009] (3) The material obtained in step (2) is centrifuged to achieve solid-liquid separation, wherein the solid state is maintained as an interwoven skeleton structure formed by the growth of silicon phase and iron phase, while the silicon-aluminum alloy phase in the gap of the skeleton structure flows out through the filter pores in the form of liquid, and after cooling and solidification, a cast aluminum-silicon alloy that meets industrial standards is obtained.
[0010] After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
[0011] Preferably, the gradient cooling in step (2) comprises: in the first stage, cooling the temperature to 850-1150°C at a cooling rate of 5-15°C / min and keeping the temperature for 20-60min; in the second stage, cooling the temperature to 700-900°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min; in the third stage, cooling the temperature to 600-750°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min; in the fourth stage, cooling the temperature to 577-650°C at a cooling rate of 0.5-10°C / min and keeping the temperature for 20-60min.
[0012] Preferably, the material obtained in step (2) is heated to 577-700° C., kept warm for 0-360 min, and then centrifuged.
[0013] In the above method, the silicon-alumina raw material in step (1) can be one or a mixture of natural silicon-alumina minerals, solid waste containing silicon-alumina, or artificially synthesized silicon-alumina raw materials, wherein the natural silicon-alumina minerals include bauxite, kaolinite, albite, potassium feldspar, etc., and the solid waste containing silicon-alumina includes bauxite flotation tailings, coal gangue, fly ash, shale slag, etc.
[0014] In the above method, the carbonaceous reducing agent in step (1) includes coal, petroleum coke, calcined anthracite, coke, metallurgical coke, one of which or a mixture of several thereof.
[0015] In the above method, the amount of the carbonaceous reducing agent in step (1) is 90-95% of the required reducing agent. If it exceeds 95%, the metal carbides (especially aluminum carbide) in the alloy will increase, which will not only reduce the alloy yield but also affect the stability of arc furnace smelting.
[0016] In the above method, the mass of the binder added in step (1) is 5-10% of the mixed material, the pelletizing pressure is 50-150 MPa, the pellet drying temperature is 150-200°C, and the moisture content of the pellets after drying is not more than 1%.
[0017] In the above method, the reduction reaction temperature in the electric arc furnace in step (1) is 2200-2500°C.
[0018] In the above method, the interwoven skeleton structure described in step (2) is a skeleton structure constructed by silicon grains and iron phase grains, which still retains the macroscopic structure of the aluminum-silicon-iron alloy described in step (1) to a certain extent in appearance after centrifugal treatment, but is loose and porous inside; the gaps in the skeleton structure are filled with aluminum-silicon alloy similar to a binder.
[0019] In the above method, the silicon phase in the interwoven skeleton structure is mainly composed of silicon element.
[0020] In the above method, the Fe mass content of the iron phase in the interwoven skeleton structure is 9.7-65%, the Al mass content is 10-68%, and the Si mass content is 12-30%.
[0021] In the above method, the physical composition of the iron phase in the interwoven skeleton structure is mainly one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2.
[0022] In the above method, the centrifugal treatment supergravity coefficient in step (3) is 50 to 500 g, and the separation time is 30 to 360 min.
[0023] The cooling mechanism of the present invention is:
[0024] When the melt is cooled, solidification phases gradually precipitate from the material, and the following steps are performed:
[0025] L→Si
[0026] L→Si+Al3FeSi2
[0027] L+Al3FeSi2→Al4FeSi+Si
[0028] L→Al+Si+Al4FeSi
[0029] First, in the primary crystallization zone of silicon, when the melt begins to cool down, the elemental Si phase will precipitate first as the temperature continues to drop; then, after entering the iron-rich phase zone, Al3FeSi2 also begins to precipitate; when the temperature continues to drop, there will be a melting process, that is, the phase and the remaining liquid phase melt to form Al4FeSi phase and elemental silicon; finally, when the temperature reaches the low eutectic point temperature of the system, the liquid phase will completely solidify and precipitate as elemental aluminum, elemental silicon and Al4FeSi phase.
[0030] According to the ratio of aluminum, silicon and iron elements in the raw materials, the cooling and condensation process is different. In particular, when the melt cooling mechanism is precisely controlled, the grain size of each solidified phase can be effectively controlled, so that the silicon phase and iron-rich phase with larger grain size can be obtained after full growth, which provides the possibility for the effective separation of the subsequent silicon phase and iron phase. At the same time, by adjusting the holding time and cooling rate of each temperature zone, the content ratio of the iron-rich phase Al3FeSi2 and Al4FeSi phase can be effectively adjusted to increase the content of the iron-rich phase Al3FeSi2 in the final solid phase. Due to the obvious difference in the morphology of the iron-rich phase Al3FeSi2 and Al4FeSi grains, the Al3FeSi2 phase is more likely to grow into coarse grains, while the opposite phase Al4FeSi phase tends to grow into fine needles. Needle-shaped grains are very easy to break into smaller particles during the subsequent separation of silicon phase and iron phase, which makes it impossible to separate the two phases through the density difference between the iron phase and the silicon phase, and it is impossible to effectively obtain high value-added single silicon products. However, when the iron-rich phase Al3FeSi2 is dominant in the product, phase separation can be effectively achieved by controlling the large-particle iron-rich phase and silicon phase and utilizing the density difference between the two phases.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. During the cooling and crystallization process of the aluminum-silicon-iron melt, the silicon phase precipitates and grows at high temperature; as the temperature decreases, the iron phase begins to precipitate and interweaves with the silicon phase to form a unique skeleton structure; as the temperature continues to drop, the remaining aluminum-silicon alloy melt solidifies and exists in the skeleton gaps formed by the silicon phase and the iron phase to form a solid block;
[0033] 2. In the process of forming the interwoven framework of silicon phase and iron phase, the aluminum silicon iron melt is gradually cooled or kept warm by precisely controlling the cooling mechanism, so as to control the size, morphology, phase composition and element composition of the crystal morphology of silicon phase and iron phase and the internal organizational structure of the alloy;
[0034] 3. During the cooling process of the aluminum-silicon-ferrosilicon melt, the silicon phase first precipitates at high temperature. By controlling the cooling rate, insulation temperature and time, the silicon phase gradually grows to a suitable size, which is more conducive to subsequent separation and extraction;
[0035] 4. According to the ratio of aluminum, silicon and iron in the raw materials, a suitable temperature zone is selected for heat preservation or gradient cooling, and the appropriate heat preservation time and cooling rate are matched to effectively realize the regulation of the phase composition of the iron phase. The precipitated iron phase can be one or more of Al4FeSi, Al3FeSi2, Al2Fe5Si5, Al9Fe5Si5, and Al3Fe3Si2; and through the adjustment of the cooling process, the particle size and growth morphology of the iron phase can be effectively regulated during the transformation of different crystal phases, providing favorable conditions for the subsequent separation of silicon phase and iron phase;
[0036] 5. After strict temperature reduction control, the iron phase can grow into large-sized grains, and effectively improve the previous needle-shaped growth orientation, making it possible to separate silicon and iron. Combined with the density difference between the silicon phase and the iron phase, polysilicon products and iron-rich phase products can be obtained by gravity separation methods such as cyclone troughs and shaking tables. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a photo of the cast aluminum-silicon alloy obtained in Example 1. DETAILED DESCRIPTION
[0038] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0039] Example 1
[0040] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.78%, the mass fraction of SiO2 is 50.15%, and the mass fraction of Fe2O3 is 1.69%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine at a pelletizing pressure of 100MPa, dry and dehydrate the prepared pellets at 120℃ to obtain dry lumps, with a moisture content of no more than 1%, and then put the dry lumps into an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 1000℃ at 10℃ / min; keeping at 1000℃ for 30min; cooling to 800℃ at 1.5℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 600℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into the hanging basket, and the centrifuge was started at 600°C, the super gravity coefficient was 200g, and the separation time was 180min. The melt was separated by a porous filter plate, and the melt was cooled and solidified to obtain a cast aluminum-silicon alloy that meets industrial standards (such as Figure 1 As shown in Table 1), the Fe mass fraction is 0.87% and the Si mass fraction is 12.78% (as shown in Table 1). Table 1 shows the content of iron and silicon elements in the cast silicon aluminum alloy obtained in Examples 1-4.
[0041] Example 2
[0042] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.71 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 42.96%, the mass fraction of SiO2 is 51.07%, and the mass fraction of Fe2O3 is 1.54%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials. Then, the mixed materials are made into pellets in a pelletizing machine, and the pelletizing press is used. The pressure is 100MPa, and the prepared pellets are dried and dehydrated at 120℃ to obtain dry lumps, with a moisture content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction, with a smelting temperature of 2200-2500℃. When the molten aluminum silicon iron alloy melt is cooled to 1400℃, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 900℃ at 10℃ / min; keeping at 900℃ for 30min; cooling to 750℃ at 1℃ / min; cooling to 700℃ at 10℃ / min; keeping at 700℃ for 30min; cooling to 650℃ at 2℃ / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.89% and the Si mass fraction was 12.85%.
[0043] Example 3
[0044] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.75 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 43.25%, the mass fraction of SiO2 is 47.56%, and the mass fraction of Fe2O3 is 4.45%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with a sulfite pulp binder and 10% of water to mix the materials, and then the mixed materials are made into a briquette machine. The pellets are formed at a pressure of 100 MPa. The prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control, cooling to 950°C at 10°C / min; keeping at 950°C for 30min; cooling to 850°C at 1°C / min; keeping at 850°C for 30min; cooling to 600°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 600°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 0.82% and the Si mass fraction was 11.96%.
[0045] Example 4
[0046] The gangue and coal crushed to a particle size less than 100 mesh are uniformly mixed in a mass ratio of 1:0.79 to form a mixed material, wherein the mass fraction of Al2O3 in the gangue is 40.35%, the mass fraction of SiO2 is 45.89%, and the mass fraction of Fe2O3 is 8.22%, and the mass fraction of Al2O3 in the coal is 46.01%, the mass fraction of SiO2 is 45.10%, and the mass fraction of Fe2O3 is 4.75%. Then, 6% of the mass of the mixed material is added with sulfite pulp binder and 10% of water to mix the mixed material, and then the mixed material is placed in a briquetting machine. The pellets are made at a pressure of 100 MPa, and the prepared pellets are dried and dehydrated at 120°C to obtain dry lumps, with a water content of no more than 1%. The dry lumps are then placed in an electric arc furnace for reduction reaction at a smelting temperature of 2200-2500°C. When the molten aluminum silicon iron alloy melt is cooled to 1400°C, it is cast in a mold and placed in a tunnel kiln for gradient temperature control. The gradient temperature control is carried out, cooling to 950°C at 10°C / min; cooling to 850°C at 1°C / min; cooling to 800°C at 10°C / min; and cooling to 650°C at 2°C / min. At this time, a skeleton structure composed of large flaky silicon phases and coarse granular iron phases has been formed inside the sample. The above samples were directly loaded into a hanging basket, placed in an ultragravity centrifuge equipped with a heating device, and the centrifuge was started at 650°C. The ultragravity coefficient was 200g, the separation time was 180min, and the melt was separated by a porous filter plate. After the melt was cooled and solidified, a cast aluminum-silicon alloy that met industrial standards was obtained, in which the Fe mass fraction was 1.45% and the Si mass fraction was 14.36%.
[0047] Compared with cooling to room temperature and then heating, the direct centrifugation process saves one heating process and has lower production costs.
[0048] Table 1
[0049] sample Fe(%) Si(%) Example 1 0.87 12.78 Example 2 0.89 12.85 Example 3 0.82 11.96 Example 4 1.45 14.36
Claims
1. A method for producing cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials, characterized in that: The steps include: (1) crushing the silicon-aluminum raw material and the carbonaceous reducing agent, adding a binder and water to mix them evenly, forming agglomerates, drying to obtain dry agglomerates, and then putting them into an electric arc furnace for reduction reaction to obtain a single-element aluminum-ferrosilicon melt; (2) Under controlled cooling conditions, the obtained aluminum silicon iron melt is subjected to gradient cooling, wherein the gradient cooling includes the following stages: in the first stage, the temperature is reduced to 800-1300° C. at a cooling rate of 1-20° C. / min and kept at this temperature for 10-200 min; in the second stage, the temperature is reduced to 650-1000° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 10-200 min; in the third stage, the temperature is reduced to 600-850° C. at a cooling rate of 0.1-20° C. / min and kept at this temperature for 0-200 min; in the fourth stage, the temperature is reduced to 577-650° C. at a cooling rate of 0.1-20° C. / min; (3) The material obtained in step (2) is centrifuged to achieve solid-liquid separation, wherein the solid state is maintained as an interwoven skeleton structure formed by the growth of silicon phase and iron phase, while the silicon-aluminum alloy phase in the gap of the skeleton structure flows out through the filter pores in the form of liquid, and after cooling and solidification, a cast aluminum-silicon alloy that meets industrial standards is obtained.
2. The method for producing cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: After the silicon-aluminum raw material and the carbonaceous reducing agent in step (1) are added together, the ratio of aluminum, silicon and iron is as follows: the aluminum content is 10-88.3wt.%, the silicon content is 11.7-90wt.%, the iron content is 0.01-26.0wt.%, and the iron content is ≤(45.64-0.52Al)wt.% and ≤(40.63-0.41Si)wt.%.
3. The method for producing cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: The gradient cooling in step (2) includes: in the first stage, the temperature is lowered to 850-1150°C at a cooling rate of 5-15°C / min and kept warm for 20-60min; in the second stage, the temperature is lowered to 700-900°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min; in the third stage, the temperature is lowered to 600-750°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min; in the fourth stage, the temperature is lowered to 577-650°C at a cooling rate of 0.5-10°C / min and kept warm for 20-60min.
4. The method for producing cast aluminum-silicon alloy by centrifugation with precise gradient cooling of aluminum-silicon raw materials according to claim 1, characterized in that: In step (3), the material obtained in step (2) is heated to 577-700° C., kept warm for 0-360 min, and then centrifuged.
Citation Information
Patent Citations
Method for preparing aluminum-silicon-iron alloy from high-aluminum coal gangue and conducting graded purification
CN113913621A
A method for preparing aluminum-silicon-iron alloy using high-aluminum fly ash and grading purification
CN114480855B